Reservation Wages and the Wage Flexibility Puzzle - Koenig, Felix; Manning, Alan; Petrongolo, Barbara (The Review of Economics and Statistics, 2024)
Using micro data for the UK and Germany, we provide novel evidence on the cyclical properties of reservation wages and estimate that wages and reservation wages are characterised by moderate and very similar degrees of cyclicality. Several job search models that quantitatively match the cyclicality of wages tend to overpredict the cyclicality in reservation wages. We show that this puzzle can be addressed when reservation wages display backward-looking reference dependence. Model calibrations that allow for reference dependence match the empirically observed cyclicality of wages and reservation wages for plausible value of all other model parameters.